TECHNICAL AND VOCATIONAL SKILLS COMPETITIVENESS AS A DETERMINANT OF DEMAND FOR TECHNICAL AND VOCATIONAL TRAINING AMONG THE YOUTH IN KAJIADO COUNTY, KENYA - Sankale, James; Sakwa, Prof. Maurice M.; Ndegwah, Dr. David J. (African Journal of Education and Practice, 2017)
Purpose: The study sought to investigate skills competitiveness as a determinant for the demand for technical and vocational training among the youth in Kajiado County. Methodology: The study used a mixed method design of both qualitative and quantitative methods for the purposes of triangulation. Quantitative and qualitative forms of data were linked for three reasons: First, for confirming or corroborating each other via triangulation; second, for elaborating or developing analysis, providing richer details and third, for initiating new lines of thinking through attention to new ideas coming up, as well as and providing fresh insight (Rosmann and Wilson (quoted in Miles & Huberman, 1994). The study was confined to the natural settings and attempted to interpret phenomenon in terms of the meaning that people brought as asserted by Denzin and Lincoln (2005). In executing the study, a descriptive cross- sectional survey was applied as the quantitative research design. In addition, phenomenological approach was chosen due to its strength in enabling researchers to gain a depth of understanding of the cases and situation studied. The target population for the study comprised of all students enrolled in three polytechnics in Kajiado County (namely Isinya, Namelok and Entasopia). Moreover, the management of the three polytechnics was also part of the population for the interviews and focus group discussions. The qualitative findings complemented the quantitative findings for a more comprehensive understanding of the issues explored in the study. Findings: TVET skills were highly affirmed to be greatly suitable for employment. Respondents also attested that it is easy to perfect the use of TVET skills and apply them. Another highly rated indicator was the respect and preference the labour market accords to persons with TVET skills. Suitability of the TVET skills in the labor market was further approved by most of the informants who were of the opinion that, once the trainees are given the necessary technical skills and provided with the basic tools for the job, then they can perform. Some participants expressed strong optimism in the applicability of TVET skills in the market. However, when further probed, it was evident that the polytechnic administration does not create enough awareness to the local community on the courses offered. From the findings, it can be inferred that skills competitiveness of TVET course is key in determining the demand for the course. Unique contribution to theory, practice and policy: To link skills development and world of work government should incorporate incubation centres within training institution as well as enhance mentorship programmes. These centres may have programmes designed to empower TVET graduates to apply the skills learnt in empowering themselves. These centres should provide start up kits to upon completion of the mentorship programme.